(untitled) (Képzés és Gyakorlat : Neveléstudományi folyóirat, 2007)
This paper analyzes visions and debates over the ‘woman question’ in Nemzeti Nőnevelés (National Female Education) (NN) (1879-1919), the journal of women’s education, with special emphasis on secondary-level education for girls. Secondary-level education for girls in Hungary was institutionalized in this period, the era of the Dual Monarchy. NN is important with respect to women’s education and the women’s movement, because before an ‘organized’ women’s movement existed in Hungary, it was the forum where ideas and experiences about girls’ education could be exchanged and where some social initiatives were mentioned for the first time. NN aimed to be a ‘neutral’ forum, which meant that very diverse authors could publish in it, regardless of their point of view, though NN had a clear set of values and perspectives as reference points. In this way NN represented various opinions that were present in the society at that time. In the analysis special emphasis is placed on the visions and debates about secondary-level education for girls, which characterized NN on the perspectives, on shaping and reforming the diverse school types and their functions within the system of secondary-level education for girls. The paper thus is intended to contribute to the existing literature by adding a more complex picture of and deeper insights into contemporary discourse and debate about the ‘woman question’, and women’s secondary education.